Arsenic speciation in marine sediments: A comparison between two sequential extraction procedures. Issue 8 (17th November 2018) - Bettoschi, Alexandre; Marrucci, Alessandro; Marras, Barbara; Atzori, Marco; Schintu, Marco
ABSTRACT: Arsenic distribution and mobility in marine sediments was investigated by means of total extraction and two sequential extraction procedures i.e. a modified sequential extraction procedure proposed by the European Standard, Measurementand Testing (SM&T) program, formerly the Community Bureau of Reference (BCR) procedure and a five steps sequential extraction based on the Wenzel extraction procedure, called modified Wenzel extraction. Sediments were collected from Cagliari's harbour and Cagliari's gulf, in Western Mediterranean Sea, Italy. The modified Wenzel extraction provided a more detailed As binding pattern and turned out to be much more appropriate than the modified SM&T procedure for gaining information regarding the mobilization of As within marine sediments. In the harbour, the largest part of As is contained in the residual fraction. At the contrary, As concentration, which is higher in the Cagliari's gulf, is primarily associated with amorphous and crystalline hydrous Fe(Mn, Al) oxide. Moreover, this study suggests the possibility to segregate different types of marine sediments depending of human or industrial activities and to trace As contaminated marine sediments to determine the origin of contamination following the percentile of As contained in each extraction steps.